Response to "Vulnerability and resistance in the United Kingdom's smart meter transition". (January 2019) - Shipworth, David; Fell, Michael J.; Elam, Simon
Abstract: Sovacool et al. (2017) consider and critique the Smart Metering Implementation Programme (SMIP) in the United Kingdom. In this response we highlight a number of areas where we believe it would have been helpful for readers to see additional information. These relate to three areas: how the authors reported on the methods used in their study; how the Programme is addressing technical challenges; and how the Programme is engaging with people in vulnerable situations. We also point out areas where we see emerging challenges, such as engaging non-traditional stakeholders, and how organizations which want to use smart meter data in the public interest might encounter barriers in meeting the demands of the Smart Energy Code.